As práticas avaliativas no processo de formação: Estudo sob o enfoque da Teoria Histórico-Cultural - Santos, Gracielly Vieira dos (2019)
To reflect on the evaluative practices in the schooling process, the study aimed to analyze the conceptions and evaluative practices of teachers and their impacts on the formation of students of the accounting science course in the light of Lev Vygotsky's Historical-Cultural Theory. We selected students from the Accounting course at an intermediate stage of the course (2nd, 3rd and 4th year) with the participation of 68 respondents from the questionnaire originated from the study by Berbel et l., (2001), and also It was attended by 13 teachers interviewed from the accounting board of a state university of Paraná, considering the classificatory and formative conceptions of the evaluation. The collected data were analyzed with the aid of SPSS 21 and Atlas TI 7.0 software, through semantic differential analysis and content analysis. The data found point to the perception of the students about the impact of evaluations on their formations in both positive and negative. Regarding the pedagogical dimension of the evaluation, students assumed that the evaluations had positive impacts on their training processes, regarding the emotional dimension, they realized that the aspects pertaining to this dimension had a positive and negative impact on their training and when dealing with the dimension. ethics students considered that the inherent aspects of this dimension had a negative impact on their training. Regarding the teaching conceptions related to the evaluation, a predominance of the classification perspective of the evaluation was observed. Analyzing the responses of teachers and students, through the categories “contradiction”, “totality” and “mediation”, derived from Lev Vygotsky's Historical-Cultural Theory, we can understand how the evaluative practices impacted on the formation of the students. students of the Accounting Science Course. The first category, "contradiction", informs us The phenomenon "evaluation" needs to move to overcome the barrier of classificatory and regulatory instrument and become an element of reach of emotional and ethical factors. For the second category, “totality” we can highlight the historical marks imprinted on their teachers' life trajectories interfere with the way they evaluate them, either by limiting or diversifying the evaluation instruments. Finally, the category “mediation” informs us that the diversification of assessment instruments provides greater interaction with students and recognizing that development occurs through interaction between subjects. The research findings show that there are evaluative practices developed by teachers that need to be repeated; there are those that need to be modified; and there are those that need to be eliminated in the name of student education directed toward the constitution of a more satisfied student who understands himself or herself more prepared for life.